In-Operando X-ray Tomography Study of Lithiation Induced Delamination of Si Based Anodes for Lithium-Ion Batteries - Tariq,F; Yufit,V; Eastwood,DS; Merla,Y; Biton,M; Wu,B; Chen,Z; Freedman,K; Offer,GJ; Peled,E; Lee,PD; Golodnitsky,D; et al. (Electrochemistry Letters, 2014)
Silicon-Lithium based rechargeable batteries offer high gravimetric capacity. However cycle life and electrode microstructure failure mechanisms remain poorly understood. Here we present an X-ray tomography method to investigate in-operando lithiation induced stress cracking leading to the delamination of a composite Si based electrode. Simultaneous voltage measurements show increased cell resistance correlating with severe delamination and microstructural changes. 3D analysis revealed 44.1% loss of the initial electrode-current collector area after 1 hour of operation at 2.4 mA/cm2 and a 21.2% increase in new anode surface area. The work represents a new basis for future investigation of Si based anodes.